Армянско-русский словарь глагольных управлений (АРСГУ) - Маилян, А.; Манукян, Ж.; Меликян, Н.; Мхитарян, С.; Фельдман, Е. (Зангак-97)
The main task of the publication is introducing the model of an unpublished Armenian–Russian dictionary of verbal government to linguistically oriented public. Three lexicographic entries introducing the verbal government of the following Armenian verbs անցնել, ասել, բաժանել and their Russian equivalents are given. These entries are provided with comment. There is a detailed preface giving the compiling principals of the dictionary based on the verb centric theory of the sentence. The verb, being the apex of the sentence, generates the tree, bifurcation of which takes place on the basis of the verb valency. The verb valency potential is represented in the dictionary in the form of patterns of the verbal government. The publication of the project is to be continued and the conclusions about similarities and distinctions in verbal government schemes (in compared languages) will be drawn after the work is completed.
Keywords: Армянско-русский словарь; Словарь глагольных управлений; Языкознание